2016
DOI: 10.2741/4424
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for Carom complex signaling and function by database mining

Abstract: Carom is a novel protein that regulates membrane curvature and transmits pathophysiological signaling. The tissue expression of Carom is unclear and its functional role and signaling are unknown. We employed a group of combined database mining strategies and established a working model of Carom signaling. We identified 26 Carom partners and established their expression profiles in human and mouse tissues. We classified three tiers of tissues for Carom/partner expression and found lymph node was the tier 1 tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It interacts with proline-rich proteins, such as adaptor and signaling proteins, via its C-terminal SH3 domains to form a functional complex at cellular membranes. Based on their endocytosis-related function reported in the literature, we selected 9 proteins from 26 Carom partners we previously identified, and termed them as Carom endocytic partners (Table 3) (32). It was reported that these Carom endocytic partners played important role in regulating actin polymerization, endocytic vesicle formation and protein ubiquitination.…”
Section: Resultsmentioning
confidence: 99%
“…It interacts with proline-rich proteins, such as adaptor and signaling proteins, via its C-terminal SH3 domains to form a functional complex at cellular membranes. Based on their endocytosis-related function reported in the literature, we selected 9 proteins from 26 Carom partners we previously identified, and termed them as Carom endocytic partners (Table 3) (32). It was reported that these Carom endocytic partners played important role in regulating actin polymerization, endocytic vesicle formation and protein ubiquitination.…”
Section: Resultsmentioning
confidence: 99%